Evaluation of Diagnostic Methods Used in Drowning - Arslan, Muhammet Mustafa; Kar, Hakan; Akcan, Ramazan; Çekin, Necmi (The Bulletin of Legal Medicine, 2005)
Dead bodies found in water causes a misconception that these deaths occurred secondary to drowning and usually originated from accidents. Diagnostic criteria of drowning are controversial. Studies about diagnostic methods concerning drowning will be compared and discussed in the present article. Data obtained from studies concerning dead bodies found in water are discussed in detail. However no specific finding which can point out drowning was determined. Detailed forensic examination and scene investigation have considerable contributions for accurate diagnosis. Early and appropriate autopsy is required to be performed in such cases. Key Words: Drowning, autopsy, diatom, immunohistochemistry